Genetic Variation in Angiotensin II Type 1 Receptor Is Linked to Lipid Levels and Hepatic Steatosis in Alcohol-Associated Liver Disease, but Not to Cirrhosis or Hepatocellular Carcinoma - Hans Dieter Nischalke; Franziska Schmalz; Janett Fischer; Christine Möller; Madlen Matz-Soja; Benjamin Krämer; Bettina Langhans; Jacob Nattermann; Thomas Berg; Christian P. Strassburg; Philipp Lutz (Gastroenterology Insights, 2024)
Background: Development of cirrhosis and hepatocellular carcinoma (HCC) in patients with high alcohol intake is modulated by genetic predispositions. Genetic variation in angiotensin II type 1 receptor (AGTR1) has been described as a risk factor for non-alcoholic fatty liver disease in Asian patients. Methods: We analysed Caucasian patients with alcohol–associated cirrhosis without (n = 238) and with (n = 339) HCC, healthy controls (n = 200), and HCV–infected cirrhotic patients with and without HCC (n = 263) for association with the polymorphisms rs3772622 and rs2276736 in AGTR1. Results: Rs2276736 in AGTR1 was associated with both low–density lipoprotein (LDL) cholesterol levels and hepatic steatosis in patients with alcohol–associated liver disease. The distribution of genotypes for both rs3772622 and rs2276736 in AGTR1 were comparable between controls, cirrhosis patients, and those with HCC. Minor allele frequencies were 32% (44%) in healthy controls, 35%/34% (46%/45%) in alcohol–associated liver disease without/with HCC and 31%/38% (43%/39%) in HCV cirrhosis and HCV HCC, respectively. The genotype of the most important genetic risk factor for fatty liver disease, PNPLA3 I148M, did not interact with the AGTR1 polymorphisms. Conclusion: Genetic variation in AGTR1, although associated with blood lipid levels and hepatic steatosis, is not a risk factor for alcohol–associated cirrhosis or HCC in Caucasians.